Subjctive assessment of the quality of life of patients with rheumatological diseases - Tomaszewska, Katarzyna; Majchrowicz, Bożena; Szewczyk, Magdalena (Journal of Education, Health and Sport, 2021)
Background: Nowadays, rheumatic diseases are increasingly recognized as chronic diseases that lead to disability, reduced quality of life and dependence on others. They are caused by pain, stiffness and reduced mobility in the joints. Early treatment and rehabilitation can improve quality of life, prolong functional abilities and independence. Objectives: Assessment of functioning and quality of life in patients with rheumatologic diseases. Material and methods: The study group consisted of 200 patients diagnosed with rheumatological disease. The research method was the diagnostic survey method. As a technique, the survey technique was used, and the tool for collecting data from patients was a questionnaire, consisting of two parts: a questionnaire and a standardized quality of life questionnaire SF-36. Results: By far the greatest in the study group of patients were limitations in the performance of roles due to physical health (score at the average level of 96.8%) and also limitations due to emotional problems (score at the average level of 72.0%) classified as high. The severity of the study patients' limitations in physical functioning (50.6%), severity of pain (56.0%), assessment of general health (53.0%) and vitality (53.5%) were rated at medium level. The study patients' limitations in social functioning (34.8%) and mental health (46.2%) were relatively low. Conclusions: The quality of life of patients with rheumatologic diseases is rated at an average level, the physical dimension was rated worse by older people and better by people with higher education.